2006
DOI: 10.1159/000091231
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Patterns in a Small-Bodied Nocturnal Folivore (Avahi laniger) and the Influence of Leaf Chemistry: A Preliminary Study

Abstract: We present data on feeding patterns in Avahi laniger and compare these data to temporal variations in leaf chemistry. Because A. laniger is one of the smallest folivorous primates and has a monogastric stomach, we hypothesized that this lemur would display behavioural adaptations to a leaf-based diet by scheduling feeding times when leaves were of highest quality. Data were collected from May to August 2004 at the Vatoharanana site in Ranomafana National Park, Madagascar. A. laniger fed during different time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…The right composition of the different tree species might, however, be of importance. The similar-sized and nocturnal eastern woolly lemur Avahi laniger was described to feed on the leaves of 9 different tree species, with > 80% of the diet being comprised of 3 species (Faulkner & Lehman 2006), preferring young leaves with higher protein and protein-to-fiber ratios (Milton 1979, Yeager et al 1997, Chapman et al 2004). The eastern woolly lemur has also been ob served to use higher quality (high protein, low alkaloid) foods than the weasel sportive lemur L. mustelinus (Ganzhorn 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The right composition of the different tree species might, however, be of importance. The similar-sized and nocturnal eastern woolly lemur Avahi laniger was described to feed on the leaves of 9 different tree species, with > 80% of the diet being comprised of 3 species (Faulkner & Lehman 2006), preferring young leaves with higher protein and protein-to-fiber ratios (Milton 1979, Yeager et al 1997, Chapman et al 2004). The eastern woolly lemur has also been ob served to use higher quality (high protein, low alkaloid) foods than the weasel sportive lemur L. mustelinus (Ganzhorn 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the broad habitat characteristics used here may mask fine-grained responses of folivorous lemurs to spatial variations in leaf quality (protein and energy). For example, Avahi laniger is a small-bodied (0.60-1.30 kg), highly folivorous lemur that is sympatric with L. mustelinus throughout much of southeastern Madagascar [Faulkner and Lehman, 2006], except for Kalambatritra Special Reserve, in which no A. laniger have been seen but Lepilemur sp. are abundant [Irwin et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Despite A. laniger exhibiting a neutral edge response using broad edge versus interior habitats [Lehman et al, 2006a], detailed spatial data revealed that this species is most abundant within 100 m of the forest edge [Lehman et al, 2006b]. Edge-related variations in A. laniger densities are likely a result of higher protein levels in leaves near forest edges [Ganzhorn, 1995] as well as small body size and the simple monogastric stomach of this lemur [Faulkner and Lehman, 2006]. Spatial variations in protein levels should also be relevant to L. mustelinus.…”
Section: Discussionmentioning
confidence: 99%
“…Avahi laniger FL Leaves, buds, twigs [Ganzhorn et al, 1985;Harcourt, 1991;Faulkner and Lehman, 2006] Indri indri FL Young leaves, fruit, flowers and seeds [Powzyck, 1998] Propithecus edwardsi FL Leaves, seeds, fruit [Hemingway, 1998;Powzyck, 1998] Propithecus verreauxi FL Leaves, wood, bark stems, fruit, flowers [Richard, 1974;Richard, 1978;Sailer et al, 1985;Yamashita, 2002;Simmen et al, 2003 [Sussman, 1974;Sailer et al, 1985;Sauther, 1991;Yamashita, 2002;Simmen et al, 2003] Varecia variegata FR Mainly fruit [Morland, 1992;Balko, 1998;Ratsimbazafy, 2002] Lepilemuridae Lepilemur mustelinus FL Mainly leaves, some wood, bark, stems, fruit and flowers [Richard, 1987;Lehman, 2007] each species. Finally, a univariate discriminant function analysis (SPSS v. 14) was used to derive posterior probabilities of membership in the closest dietary group.…”
Section: Microcebus Murinusmentioning
confidence: 99%